Social Cognition in Adult ADHD: A Systematic Review - Morellini, Lucia; Ceroni, Martino; Rossi, Stefania; Zerboni, Giorgia; Rege-Colet, Laura; Biglia, Elena; Morese, Rosalba; Sacco, Leonardo (Frontiers in Psychology, 2022)
The aim of this systematic review was to collect and align the research on social cognition impairments in adults with Attention-deficit/hyperactivity disorder (ADHD). In particular, we selected and analyzed papers on emotion recognition and processing, Theory of Mind (TOM), empathy, and other facets of social cognition as decision making. We identified 16 papers published between 2012 and 2022 which meet inclusion criteria. Papers search, selection, and extraction followed the PRISMA guidelines. In order to summarize data from papers, we used a narrative synthesis approach. Results show different evidence of impairment in social cognition domains in adults with ADHD. Our systematic review suggests the importance of promoting more research on this topic because it is essential to keep in mind that social cognition plays a central role in socialization and social relationships.